2021
DOI: 10.1016/j.jaci.2020.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the 15-lipoxygenase pathway in aspirin-exacerbated respiratory disease

Abstract: Background: Aspirin-exacerbated respiratory disease (AERD) is characterized by asthma, chronic rhinosinusitis with nasal polyps (CRSwNP), and an intolerance of medications that inhibit cyclooxygenase-1. Patients with AERD have more severe upper and lower respiratory tract disease than do aspirintolerant patients with CRSwNP. A dysregulation in arachidonic acid metabolism is thought to contribute to the enhanced sinonasal inflammation in AERD. Objective: Our aim was to utilize an unbiased approach investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 46 publications
2
70
1
4
Order By: Relevance
“…A missense variant in ALOX15 (p.Thr560Met), resulting in near total loss of 15‐lipoxygenase activity, showed the largest protective effects against the risk of both NP and CRS. A recent study using single‐cell RNA sequencing has shown that ALOX15 was predominantly expressed by apical epithelial cells and significantly increased in NPs of N‐ERD patients compared to NPs of CRSwNP patients 44 . The expression levels significantly correlated with sinus disease severity and were associated with the presence of asthma.…”
Section: Genetic Background Of Adult‐onset Eosinophilic Airway Diseasesmentioning
confidence: 95%
See 3 more Smart Citations
“…A missense variant in ALOX15 (p.Thr560Met), resulting in near total loss of 15‐lipoxygenase activity, showed the largest protective effects against the risk of both NP and CRS. A recent study using single‐cell RNA sequencing has shown that ALOX15 was predominantly expressed by apical epithelial cells and significantly increased in NPs of N‐ERD patients compared to NPs of CRSwNP patients 44 . The expression levels significantly correlated with sinus disease severity and were associated with the presence of asthma.…”
Section: Genetic Background Of Adult‐onset Eosinophilic Airway Diseasesmentioning
confidence: 95%
“…The expression levels significantly correlated with sinus disease severity and were associated with the presence of asthma. 44 A downstream product of 15‐lipoxygenase (15‐oxo‐ETE) was elevated in NP compared with that in healthy sinonasal tissue, and these findings suggest the involvement and interactions of epithelial and mast cells in the transmetabolic process 44 . IL‐13 further contributes to tissue eosinophilia through eotaxin‐3 production from fibroblasts and epithelial cells, 45 reportedly in a 15‐lipoxygenase‐1‐dependent manner 46 …”
Section: Genetic Background Of Adult‐onset Eosinophilic Airway Diseasesmentioning
confidence: 98%
See 2 more Smart Citations
“…A novel mediator, 15-oxo-ETE was also recently identified in AERD that is a product of the 15-lipoxygenase pathway. 26 MCs appear to be critical in this process using MC-derived hematopoietic PGD2 synthase (HPGDS) to generate 15-oxo-ETE.…”
Section: Pathogenesis Of MC Activation In Aerdmentioning
confidence: 99%